Characterizing solute hydrogen and hydrides in pure and alloyed titanium at the atomic scale. (15th May 2018) - Chang, Yanhong; Breen, Andrew J.; Tarzimoghadam, Zahra; Kürnsteiner, Philipp; Gardner, Hazel; Ackerman, Abigail; Radecka, Anna; Bagot, Paul A.J.; Lu, Wenjun; Li, Tong; Jägle, Eric A.; Herbig, Michael; et al.
Abstract: Ti and its alloys have a high affinity for hydrogen and are typical hydride formers. Ti-hydride are brittle phases which probably cause premature failure of Ti-alloys. Here, we used atom probe tomography and electron microscopy to investigate the hydrogen distribution in a set of specimens of commercially pure Ti, model and commercial Ti-alloys. Although likely partly introduced during specimen preparation with the focused-ion beam, we show formation of Ti-hydrides along α grain boundaries and α/β phase boundaries in commercial pure Ti and α+β binary model alloys. No hydrides are observed in the α phase in alloys with Al addition or quenched-in Mo supersaturation. Graphical abstract: Image 1